Mutanaqishah Musyarakah Contract: A Solution To Infrastructure Investment Syndication Financing - zulfikar, Zulfikar; Asmuni, Asmuni; Anggraini, Tuti (Universitas Alma Ata, 2023)
This study aims to find an alternative in business activities in Islamic financial institutions, especially in Islamic banking, where when the use of a single contract in a business contract occurs, it still creates weaknesses in the process of cooperation between the customer and the bank. So that it needs to be analyzed further the use of a single contract in a business contract for long-term financing is still relevant for business purposes. This single contract in financing is in great demand by Islamic financial institutions because it is simple and simple in business activities, and of course, it can provide certainty of future income, what we often know is natural certainty contracts. However, along the way, cooperation in natural certainty contracts is not always suitable for long-term financing and the needs of large projects. This research also looks at the phenomenon of problems that occur in the cooperation of a single contract, one of which is the Murabaha contract. Due to this problem, Islamic banks have started to implement the use of multiple contracts or hybrid contracts in long-term investment financing cooperation, especially in the infrastructure sector, because the nature of business contracts is more flexible, can be reviewed, and provides the principle of fairness